The Importance-Performance Matrix Analysis in Partial Least Square Structural Equation Modeling (PLS-SEM) with Smartpls 2.0 M3 - Ahmad, Sabri; Afthanorhan, Wan Mohamad Asyraf Bin Wan (International Journal of Mathematical Research, 2014)
The Important-Performance Matrix Analysis (IPMA) is widely used in analytical technique that yields prescription for the management of customer satisfaction. IPA is a two-dimensional grid based on importance and performance of customer satisfaction. Yet, this paper intend to use the volunteers as a research subject to identify to what extent the strength of the relationship between exogenous and endogenous variable that can be derived. As pedagogical theoretical and past empirical studies, attribute level of performance and importance is relevance and significant. These finding reveals the capabilities of IPA towards a volunteerism program. Using Partial Least Square Structural Equation Modeling with SmartPLS 2.0, the asymmetric relationship importance and performance is provided. Futhermore, it shown that benefits factor is a major importance and performance for establishing Motivation.